Setting up of tertiary care institutes in rural India: Not the sole remedy for all maladies plaguing the health system - Richa Richa; Vishal Kumar; Sudip Bhattacharya; Sitanshu Barik; Vikash Raj (Journal of Family Medicine and Primary Care)
To achieve the goal of ‘Health for All’, the Indian government has introduced various schemes aimed at making affordable health care accessible to every citizen. However, rural, tribal, and remote areas face significant challenges due to poor infrastructure, unequal distribution of government resources, and a shortage of skilled healthcare workers. To tackle these issues, the government has focused on establishing premier tertiary care centres, including institutes of national importance like AIIMS, and upgrading existing tertiary facilities to offer specialty and super-specialty services under the Pradhan Mantri Swasthya Suraksha Yojana (PMSSY). While these efforts are crucial, they represent only one part of building a strong and equitable healthcare system that serves all, regardless of social or economic status. Our case series emphasizes the importance of a holistic approach to health care. This includes reducing poverty, strengthening infrastructure, and improving health literacy through collaborative, multipronged efforts, particularly focusing on musculoskeletal diseases. Though these initiatives will take time to show results, they are essential for creating ‘centres of excellence’ that truly address the needs of the underserved, rather than isolated ‘islands of excellence’.